Time elapsed between Zika and dengue virus infections affects antibody and T cell responses - Erick X. Pérez-Guzmán (Nature Portfolio, 2019)
Here, the authors show that the time elapsed between Zika infection and subsequent dengue virus infection affects the magnitude and durability of the antibody and cell-mediated immune responses against dengue virus, but not viremia. This research in non-human primates has implications for co-endemic regions and vaccination.